Cellular and humoral responses to an HIV DNA prime by electroporation boosted with recombinant vesicular stomatitis virus expressing HIV subtype C Env in a randomized controlled clinical trial. Issue 16 (17th April 2023) - Wilson, Gregory J.; Rodriguez, Benigno; Li, Shuying Sue; Allen, Mary; Frank, Ian; Rudnicki, Erika; Trahey, Meg; Kalams, Spyros; Hannaman, Drew; Clarke, David K.; Xu, Rong; Egan, Michael; et al.
Abstract: Background: HIV subtypes B and C together account for around 60% of HIV-1 cases worldwide. We evaluated the safety and immunogenicity of a subtype B DNA vaccine prime followed by a subtype C viral vector boost. Methods: Fourteen healthy adults received DNA plasmid encoding HIV-1 subtype B nef/tat/vif and env (n = 11) or placebo (n = 3) intramuscularly (IM) via electroporation (EP) at 0, 1, and 3 months, followed by IM injection of recombinant vesicular stomatitis virus encoding subtype C Env or placebo at 6 and 9 months. Participants were assessed for safety, tolerability of EP, and Env-specific T-cell and antibody responses. Results: EP was generally well tolerated, although some device-related adverse events did occur, and vaccine reactogenicity was mild to moderate. The vaccine stimulated Env-specific CD4 + T-cell responses in greater than 80% of recipients, and CD8 + T-cell responses in 30%. Subtype C Env-specific IgG binding antibodies (bAb) were elicited in all vaccine recipients, and antibody-dependent cell-mediated cytotoxicity (ADCC) responses to vaccine-matched subtype C targets in 80%. Negligible V1/V2 and neutralizing antibody (nAb) responses were detected. Conclusions: This prime/boost regimen was safe and tolerable, with some device-related events, and immunogenic. Although immunogenicity missed targets for an HIV vaccine, the DNA/rVSV platform may be useful for other applications. Trial registration. Clinicaltrials.gov : NCT02654080.